The effects of post-isometric relaxation and static stretch training on hamstring flexibility and its relationship to tightness among 9-11 year old school children - Liyanage, Esther (2020)
The present study was divided into two phases. Phase one aimed to identify the prevalence of hamstring tightness and to assess correlation of hamstring flexibility with physical activity, BMI and anthropometry among 9-11 years old Malaysian and Sri Lankan children. Second phase aimed to investigate the effects of post isometric relaxation and static stretch training on hamstring tightness, physical activity level and motor proficiency in same populations. The number of subjects recruited in phase one was 385 (Mean age 10.1 ± 0.7) Malaysian and 389 (Mean 9.9 ± 0.8) Sri Lankan subjects. All the subjects were assessed for anthropometry, hamstring flexibility and physical activity level revealing hamstring tightness in 43.3% and 44.1% Malaysian subjects (by passive straight leg raise test); and 32.5% and 33.2% (by back saver sit and reach test) on dominant and non-dominant side respectively. Among Sri Lankan subjects the percentage was 51.2% and 51.9% (by passive straight leg raise test) and 40.6% and 41.1% (by back saver sit and reach test) on dominant and non-dominant side respectively. There was a significant positive moderate correlation between the findings of hamstring flexibility obtained by the two test methods among Malaysian (r = 0.40–0.42) and Sri Lankan (r = 0.52–0.54) subjects (p < 0.001). There was a significant positive weak to moderate correlation between hamstring flexibility andphysical activity level among Malaysian (r = 0.31–0.33) and Sri Lankan (0.21-0.31) subjects (p < 0.001). Subjects in the “high” physical activity category obtained significantly higher scores of hamstring flexibility compared to “low” physical activity subjects in both countries (p < 0.05). The normal weight subjects obtained significantly higher hamstring flexibility scores when compared to overweight and obese children among Malaysian subjects (p < 0.001). Phase two involved 120 subjects with 60 males and 60 females with hamstring tightness identified from phase one of this study recruited in both countries for 6 weeks intervention with all parameters measured at baseline, on 3rd and 6th week. Both exercise groups showed significantly higher values for hamstring flexibility scores when compared to the control groups in Malaysian and Sri Lankan populations. Among subjects of both countries there were significant improvements in both exercise groups at the end of six weeks in motor proficiency with such difference not seen in control group. It is concluded that the post isometric relaxation stretch method was superior to static stretching in improving hamstring flexibility among Malaysian and Sri Lankan subjects which reflected in enhanced physical activity and motor proficiency in both countries among 9-11 years old sedentary children who were not elite athletes.